Asuhan Kebidanan Pada Masa Kehamilan, Persalinan, Nifas, BBL, KB Dan Gambaran Pengetahuan Ibu Tentang Persalinan Pada Ny. S G1p0a0 - Miftahul Jannah (Pusat Riset dan Inovasi Nasional, 2021)
Pregnancy is a physiological and natural condition that occurs in women. There are various complaints experienced by pregnant women during their pregnancy, one of the most common complaints is dizziness. Objective: LTA provides comprehensive midwifery care to pregnant, maternity, postpartum, BBL, neonate and family planning women using a midwifery management approach for Mrs